DESIGN OF AUTOMATIC WATERING SYSTEM FOR HYDRAULIC PLANT MAINTENANCE USING MICROCONTROLLER BASED FUZZY SET METHOD - Khairuna; Sriani; Adi Hartono; Abdul Halim Hasugian (INFOKUM, 2020)
The application of technology to agriculture provides an advantage in terms of increasing production or yields. In terms of maintaining a plant, it takes a long process, for example fertilizing, irrigation, synthesis of sunlight and others. Up to now, this work is still carried out by human labor so that it severely limits the yield or quantity of harvest. The application of technology for plant cultivation is planned to build an automatic irrigation system for hydroponic plants. Hydroponic plants are a type of plant that only need water in the process of growth. Thus a good irrigation system greatly affects the success of cultivating this type of plant. The results of this study are: First, designing a hydroponic plant maintenance system that works automatically with sensors and microcontrollers. Second, designing a control circuit using the ATMega8 Microcontroller as the system controller. And third, implementing the Fuzzy Set algorithm in the program so that the system can work properly.